Characterization of iron acquisition catalyzed by Fiu - Yang, Taihao (Kansas State University, 2022)
Under iron deficient conditions, Gram-negative bacteria like Escherichia coli secrete enterobactin, a catecholate siderophore that complexes and solubilizes iron in the extracellular environment. Ferric enterobactin (FeEnt) is the most avid natural or synthetic iron complex. It may be glucosylated (FeGEnt), and it is subject to chemical degradation and oxidation (FeEnt*). E. coli Fiu is an outer membrane protein that transports monomeric catecholate iron complexes. Using siderophore nutrition tests and radioisotope accumulation experiments, we found that Fiu preferentially recognized and transported FeEnt*. To further analyze the specificity of Fiu-mediated FeEnt* uptake, we engineered fluorescent sensors by creating Cys substitutions in the external loops of Fiu and labeled them with fluorescein maleimide. Upon binding of ferric siderophores, the surface loops of siderophore receptors undergo conformational motion that may quench attached fluorophores, allowing quantitative determinations of affinity and specificity. We screened potential ligands for Fiu and determined its binding affinities to the ferric catecholates FeEnt*, FeEnt, FeGEnt, FeDHBA, FeDHBS, and two siderophore antibiotics FeFDC and FeMB-1. To gain more insight into these binding reactions we performed computational docking experiments and molecular dynamic (MD) simulations with Fiu. The modeling studies found two potential binding sites for FeEnt* and identified residues that might participate in interactions with the iron complex. We tested these predictions by site-directed alanine scanning mutagenesis. Ala substitutions at F105, E108, D124, R142 and K739 impaired ligand binding. FeEnt* uptake by those mutants was reduced or abolished in siderophore nutrition tests. In summary, Fiu manifests specificity for the degradation products of FeEnt, but also recognizes FeEnt, FeGEnt, FeDHBS, FeDHBA,, FeFDC and Fe MB-1, confirming its importance in Gram-negative bacterial iron acquisition systems that function in colonization or pathogenesis of humans and animals. Insight into the binding and transport mechanisms of Fiu is essential to the understanding of next-generation antibiotics targeting TonB-dependent receptors like Fiu, including the recently licensed compound cefidericol (FeTroja).
Keywords: TonB-dependent transport; Fiu; CRE/ESKAPE pathogen; Fluorescent sensor; Iron acquisition